EU-Ukraine relations in the field of foreign, security and migration policy in the period of the russia’s full-scale invasion of Ukraine - Zaitseva-Kalaur, Inna; Parashcuk, Lilia; Didushyn, Vasylyna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article provides a detailed analysis of Ukraine’s relations with the EU in the field of foreign, security and migration policy during the period of Russian full-scale invasion of Ukraine. It has been established that one of the most effective measures is the imposition of sanctions, including a ban on the import of certain goods, restrictions on access to credit and other measures that contribute to the weakening of the Putin regime. Equally important is the introduction of tough restrictive measures against countries that actively cooperate with the aggressor country. The authors focus on the need for the EU to increase its overall defence capabilities in view of new challenges and threats. The study has shown that the legal aspect of temporary protection and refugee status is complex and requires a careful approach. Innovations in legislation aimed at facilitating administrative procedures and improving conditions for refugees are a step in the right direction. However, it is important to constantly adapt these mechanisms to real needs and ensure their effectiveness. The authors conclude that it is difficult to predict future decisions of the EU and its member states on temporary protection and refugee status for Ukrainians, as it depends on many factors, such as the political situation, humanitarian circumstances and internal policies of the host countries. The article outlines some possible scenarios for solving these problems, which include the extension of temporary protection; granting refugee status; diplomatic agreements and cooperation; evacuation and humanitarian programmes, etc.